2016
DOI: 10.1002/cssc.201600641
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Precursor Compositions on the Structural and Photovoltaic Properties of Spray‐Deposited Cu2ZnSnS4 Thin Films

Abstract: Pure sulfide Cu2 ZnSnS4 thin films were fabricated on Mo-coated glass substrates by facile spray deposition of aqueous precursor solutions containing Cu(NO3 )2 , Zn(NO3 )2 , Sn(CH3 SO3 )2 , and thiourea followed by annealing at 600 °C. When a precursor solution containing a stoichiometric composition of Cu, Zn, and Sn was used, the resulting Cu2 ZnSnS4 thin film contained a Cu2-x S impurity phase owing to the evaporation of Sn components during the annealing process. The Cu2-x S impurity in the Cu2 ZnSnS4 thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 59 publications
1
35
1
Order By: Relevance
“…[27] This reaction is also of high industrial importance for the productiono fc opper(II) nitrate, which is used as ap recursor for ab road variety of coppero xide and Claycop catalysts, in materialss cience and as am ild nitration reagent. [28,29] The data summarized in Table 1s how that comparable or even better yields can be obtained in the 10 liter wet scrubber than in the small scale diazotization reactions (Scheme2).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…[27] This reaction is also of high industrial importance for the productiono fc opper(II) nitrate, which is used as ap recursor for ab road variety of coppero xide and Claycop catalysts, in materialss cience and as am ild nitration reagent. [28,29] The data summarized in Table 1s how that comparable or even better yields can be obtained in the 10 liter wet scrubber than in the small scale diazotization reactions (Scheme2).…”
mentioning
confidence: 91%
“…For the synthesis of sulfasalazine, sulfanilic acid (6)w as used as starting material, as diazotization of the larger pyridinylsulfonamide (see dotted substructure of sulfasalazine (3), Figure 1) gave low yields and severals ide-reactions includingt he loss of SO 2 .I nt he next step, the diazotization reactions were transferred into a1 0liter wet scrubber miniplant( see Supporting Information for pictures of the setup). [28,29] The data summarized in Table 1s how that comparable or even better yields can be obtained in the 10 liter wet scrubber than in the small scale diazotization reactions (Scheme2). [27] This reaction is also of high industrial importance for the productiono fc opper(II) nitrate, which is used as ap recursor for ab road variety of coppero xide and Claycop catalysts, in materialss cience and as am ild nitration reagent.…”
mentioning
confidence: 99%
“…There are numerous methods for deposition of Cu 2 ZnSnGeS 4 (CZTGeS) thin films, which including the magnetron sputtering, colloidal synthesis, knife coating, solvothermal synthesis, spray pyrolysis, etc. The last method attracts a considerable attention because it is easy to implement, it has a high controllability of parameters and requires a cheap manufacturing equipment . Nevertheless, the substitution mechanism of Sn by Ge in CZTGeS thin films, obtained at different deposition temperatures by the method of spray pyrolysis, is not sufficiently studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…The last method attracts a considerable attention because it is easy to implement, it has a high controllability of parameters and requires a cheap manufacturing equipment. 18,19 Nevertheless, the substitution mechanism of Sn by Ge in CZTGeS thin films, obtained at different deposition temperatures by the method of spray pyrolysis, is not sufficiently studied yet.…”
mentioning
confidence: 99%
“…Recently, the efficiency record for pure‐sulfide CZTS has already exceeded 10% . Besides, many solution‐based methods have been reported that high‐quality CZTS film can be fabricated via non‐sputtering processes, indicating the possibility of sputtering‐free CZTS solar cells . For a typical CZTS solar cell, the fabrication of both ZnO window layer and transparent top contact relays on sputtering technique, although the fabrication of CZTS film can be solution‐processed.…”
Section: Introductionmentioning
confidence: 99%